If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -119 = 4x + -11 Reorder the terms: -119 = -11 + 4x Solving -119 = -11 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -119 + -4x = -11 + 4x + -4x Combine like terms: 4x + -4x = 0 -119 + -4x = -11 + 0 -119 + -4x = -11 Add '119' to each side of the equation. -119 + 119 + -4x = -11 + 119 Combine like terms: -119 + 119 = 0 0 + -4x = -11 + 119 -4x = -11 + 119 Combine like terms: -11 + 119 = 108 -4x = 108 Divide each side by '-4'. x = -27 Simplifying x = -27
| -3=-1-(-2) | | 3x+26=115 | | 50=2w+l | | (c-3)=16 | | 9+15=X | | 4x^2-kx+25=k | | (3tan^2x-1)(tan^2x-3)=0 | | 0.6x+7.6=6.1 | | X=1/2(4+6)3x | | 3(y+5)+9=30 | | 2x^3-21x^2+72x-53=0 | | 7y-2x-8=1 | | -6(2x-3)+3=-12x+21 | | 3a-8=52 | | 2+3X-2=180 | | (3x-36)=(2x+26) | | 8(2x-1)=2(8x+6) | | 4y=-8x+10 | | 49-3x=9-7x | | 5(x-7)=-2x+7 | | (3x-10)(8x-30)=180 | | 9w+4=5(w-8) | | (2x+3y)=3x | | 10+6h=34 | | 11x-10=(5x)-(9) | | 11/3=x-4/6 | | 7tanx+3=10tanx | | 1b+94a=94a | | 11x-10=5x-9 | | 5(5+7)=6(X+6) | | 24=(x*7)-(x*3) | | 10x+10y=2 |